2017
DOI: 10.3233/jad-170385
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Alzheimer’s Disease: Cognitive Impairment in Self-Referred and Memory Clinic-Referred Patients

Abstract: Background:Cognitive assessment is essential in tracking disease progression in AD. Presently, cohorts including preclinical at-risk participants are recruited by different means, which may bias cognitive and clinical features. We compared recruitment strategies to levels of cognitive functioning.Objective:We investigate recruitment source biases in self-referred and memory clinic-referred patient cohorts to reveal potential differences in cognitive performance and demographics among at-risk participants.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
9
1
1
Order By: Relevance
“…T-scores for the trail-making tests were calculated using published norms [34] . For the CERAD word list test, we used the normative performance of the DDI cohort control group [26] to calculate T-scores after a recent article that showed published norms not matching the younger and more educated DDI cohort [35] . A total of 42 of 74 baseline cases had available cognitive data at 2-year follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…T-scores for the trail-making tests were calculated using published norms [34] . For the CERAD word list test, we used the normative performance of the DDI cohort control group [26] to calculate T-scores after a recent article that showed published norms not matching the younger and more educated DDI cohort [35] . A total of 42 of 74 baseline cases had available cognitive data at 2-year follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…While many studies have found recruitment source differences in both AD biomarker prevalence and cognitive performance in MCI [21,24,25], studies on SCD have been inconsistent [22,24,26,27]. A recent meta-analysis found no difference in the risk of progression of SCD patients recruited by different means [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who report SCD to their general practitioner (GP) may not be referred to a memory clinic for assessment [30]. In a previous study, we found no significant cognitive differences between SCD cases recruited from memory clinics as compared to SCD cases recruited from a community sample [24].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations